2005
DOI: 10.1039/b418105k
|View full text |Cite
|
Sign up to set email alerts
|

Old Masters' lead white pigments: investigations of paintings from the 16th to the 17th century using high precision lead isotope abundance ratios

Abstract: White lead (2PbCO(3).Pb(OH)(2)), a common component in 17c. artists' painting materials, was singled out to investigate the potential of lead isotope abundance ratios in the field of authentication and origin assignment. Paintings by Peter Paul Rubens, Anthony van Dyck and other Old Masters of the Northern and Southern schools were chosen for this study. An interdisciplinary approach was chosen using both analytical instrumental methods, art technological and art historical knowledge. Minute samples taken from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
66
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(75 citation statements)
references
References 25 publications
(21 reference statements)
9
66
0
Order By: Relevance
“…In previous studies, Pb isotope ratio measurements with Tl external standardization have been used. [9][10][11] However, the deleterious effects of the matrix element on the isotope ratios measurement were observed in previous reports 10,[12][13][14][15] as well. Environmental and biological samples, such as soil, house dust, diet and blood samples contain a wide variety of matrix elements (i.e., Ca, Na, Al and Fe).…”
Section: Introductionmentioning
confidence: 85%
“…In previous studies, Pb isotope ratio measurements with Tl external standardization have been used. [9][10][11] However, the deleterious effects of the matrix element on the isotope ratios measurement were observed in previous reports 10,[12][13][14][15] as well. Environmental and biological samples, such as soil, house dust, diet and blood samples contain a wide variety of matrix elements (i.e., Ca, Na, Al and Fe).…”
Section: Introductionmentioning
confidence: 85%
“…Archaeologists can then match the isotope ratios of individual archaeological artifacts to the fingerprints of their parent ore source, such that archaeological conclusions can be drawn [18][19][20]. In some other instances, provenancing to the original ores is not aimed at, and lead isotopic analysis is used to fingerprint artifacts from a given workshop, period, or any other possible classification and to distinguish or discriminate them from one other [13,17,[21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…In case of the Flemish-Dutch painters, comparison to data from different mines revealed, that the lead originated from either Germany or England. 497 Pb isotopic analysis has also been applied for modern forensic purposes, e.g. in order to link a fired projectile to a weapon -as comprehensively assessed by Zeichner et al who carried out firearm cleaning and shooting experiments and found out that a Pb memory effect in the barrel complicates the association.…”
Section: Archaeometry and Forensicsmentioning
confidence: 98%